Penguatan Efikasi Diri Melalui Self Talk Sebagai Koping Religius - Cahyandari, Rinova (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2023)
Adolescence is a crucial period because there is a transition from childhood to adulthood. In dealing with the dynamics of stress and storms, adolescents may develop self-efficacy problems. This paper aims to reveal the potential for managing self-efficacy through religious coping using self-talk. Respondents consisted of 60 teenage students, involving 30 students in the control group and 30 students in the experimental group. This paper was compiled from experimental research with a Pretest-Posttest Control Group Design. Data collection was carried out through self-efficacy questionnaires. Data analysis using statistical tests showed that there were differences in self-efficacy between the control and experimental groups after the religious coping intervention through self-talk. Furthermore, the results show that self talk as religious coping can strengthen self-efficacy in the experimental group. As a religious coping, self-talk involves religious, and worship values and is centered on God. Self-talk can be used as a self-help technique that can change individual perceptions. Self-talk applied as religious coping can encourage individuals to re-conceptualize themselves, bring new meanings to life events, improve problem management, and encourage prosocial behavior, all of which focus on the individual's relationship as a religious being. This will direct individuals to adaptive behavior in everyday life.